Daya Hambat Asap Cair Kayu Galam terhadap Serangan Jamur pada Eceng Gondok (Eichhornia crassipes) The Effect of Galam Wood Vinegar to The Growth of Fungi on Water Hyacinth (Eichhornia crassipes) - Rais Salim (Jurnal Riset Industri Hasil Hutan, 2016)
Eichhornia crassipes is a kind of weed species that can be used as material of woven handicrafts for commercial purposes. Generally, the problems that occurred while using natural fiber material (Eichhornia crassipes) for woven handicraft products were very susceptible from moisture that triggered organisms attack such as fungal attack. The alternative materials that can be used to protect Eichhornia crassipes from fungal attack is galam wood vinegar. The purpose of this research was to determine the effect of galam wood vinegar application to Eichhornia crassipes to against fungal attack and also to determine the optimum level of wood vinegar concentration to block the fungal attack on Eichhornia crassipes. The research used two treatments i.e: concentration variations A1 (20%), A2 (25%) and A3 (30%); and soaking time variations B1 (7 hours), B2 (10 hours) and B3 (15 hours). The results was compared with the controls (0%). The field test showed that the intensity of fungal attack in the Eichhornia crassipes treated by wood vinegar from week 6 to week 10 was ranged from 2-31%. Whereas the untreated Eichhornia crassipes from week 6 to week 10 was ranged from 31.5-56%. The laboratory tests showed that the average value of weight loss of treated water hyacinth due to the attack by Aspergillus niger and Penicillium sp. ranged from 5.848-10.553% and 6.664- 11.874%, while the the average value of weight loss of untreated water hyacinth were 18.945% and 14.325%. The treatment of wood vinegar to the Eichhornia crassipes in both field tests and laboratory tests showed significant effect in resisting fungal attack so that it can be used as a preservative for Eichhornia crassipes.Keywords: water hyacinth, galam wood vinegar, penicillium sp., aspergillus niger